Monopoly of legal provisions - Sheremetyeva Anna Konstantinovna; Sofrina Zoya Fedorovna; Gamaley Artem Aleksandrovich; Novopashina Natalia Nikolaevna (SHS Web of Conferences, 2021)
The existing defect of the legal field in the form of the inconsistency of the norms that make it up, gives rise to inconsistency, imbalance of the main social regulator of social relations. Building the normative material without analysing the need to create a separate regulator, as well as the obligation to establish a relationship with existing norms, determined the significance of such a study. The definition of competition of norms is an object of scientific research quite often. However, the content of this category and its law enforcement significance, in our opinion, have not been established quite correctly. The presence of competition of norms indicates the inconsistency of legal regulators with the principles of certainty of law, fairness and stability of legal regulation, which affects the effectiveness of laws. The research patterns are due to the need for a systematic analysis of this institution in order to identify uncovered aspects in the construction of a clear, systemic and interdependent system of legal regulation. Purpose of the research. The importance of developing fundamentally new approaches to the institution of uncertainty mediated by the phenomenon of competition to overcome the imbalance of the existing legal system, in connection with the existing need to present the normative material unambiguously and clearly. Methods. In the course of the study, in combination with a complex and systemic analysis, the following general scientific methods of cognition were used: dialectical, hermeneutic, and synthesis methods, the method of ascent from the abstract to the concrete, and the method of generalization and comparison. Results and novelty. Competition of norms is the result of an incorrect construction of the system of legal norms indicating a certain artificiality of this definition regarding the possible flexibility of the legal system. In our opinion, an increase in monopoly and individualized norms will lead to a systematic nature of the normative material, as well as an increase in confidence in it on the part of all participants in legal relations. The certainty of law must become a legal axiom.